A case study of the practices and views of the providers and consumers of EFL writing classes in the English Language Institute of Saudi Western University - Abumansour, Dania Mansour (2019)
Writing is considered a key element in knowledge creation and production in higher education (Gimenez, 2012; Lillis, 2001; Matoti and Shumba, 2011). Students at university level are expected to handle writing tasks that require literacy practices such as critical thinking and be able to use the appropriate writing conventions in order to demonstrate their knowledge (Mitchell, 2000; Ramoroka, 2012; Wingate, 2006). Therefore, writing can be a challenging task for most learners at tertiary level. In the Saudi EFL context, where the current research was conducted, students experience slow progress at university level due to their poor academic writing skills (Al-Khairy, 2013). This is a common situation in many EFL contexts (e.g. Fareh, 2010; Grami, 2010; Hujailan, 2004). This ethnographic study examines student English writing practices at Saudi Western University . It investigates the understandings of the objectives and purposes of student writing in higher education of representatives of the Ministry of Higher Education, the directors of the English Language Institute, and the teaching staff and students. Participants in this study were divided into three levels: macro/meso/micro. The theoretical framework of the study is the Academic Literacies critique of the Study Skills approach as a construct (Lea and Street, 2000), while the methodological framework is drawn from Linguistic Ethnography (Rampton et al., 2004) and Bakhtin's concept of the voice of the other in the utterances of individuals, where relevant (Bakhtin, 1981, 1986). The data were derived from primary sources: interviews and classroom observation and secondary sources: institutional documents and students' written essays. The qualitative data were analysed using analytical tools from Linguistic Ethnography and Bakhtinian concepts of the institutional voice within utterances to investigate in greater depth the data and relationships between the different levels of organisation and their understandings of the role of writing in English at tertiary level. The findings of the study reveal that English writing practices at classroom level are built upon institutional concerns and cultural beliefs. These concerns and beliefs have wider implications for the institution and country than just the development of individual writing capabilities. The thesis argues that student writing pedagogy in higher education needs to take account of students' writing needs at a functional level. It also suggests that communication between the macro-level (the representatives of the Ministry of Higher Education), the meso-level (the directors of the English Language Institution) and micro-level (the staff and students of the English Language Institute) has to be established to improve the organisational structure as well as the culture of courses so that information exchanges about writing practices and student needs can flow from the bottom up to inform decision-makers at the top.